Relative rest index influences team performance and game outcomes in recent NBA competition - Pinzone, A. G.; Gant, R. W.; Magee, M. K.; Barkley, J. E.; Jajtner, A. R. (The Journal of Strength and Conditioning Research, 2026)
This investigation aimed to assess the relationship between relative rest index (RRI) and team performance and game outcomes during the prior 2 seasons of competition in the National Basketball Association (NBA). All regular season games from the 2022-23 and 2023-24 NBA seasons (N = 2,461 games) were analyzed. Relative rest index was noted as the discrepancy in rest between games between competing teams, with teams for each game placed into 1 of 5 RRI categories (<=-2, -2 to -0.5, -0.5 to 0.5, 0.5 to 2, and >=2). Point differential (DIFF), points for (PF), points allowed (PA), and game outcome (W/L) quantified team performance and game outcomes. Multilevel linear (DIFF, PF, PA) and logistic (W/L) mixed effects regression models assessed the influence of RRI on team performance, with further adjustment for competitive season, game location, opponent quality, and season portion. Greater RRI (0.5-2 and >=2) was positively associated with DIFF and W/L relative to the reference RRI category (<=-2), and teams with RRIs of -0.5 to 2 demonstrated significantly decreased PA relative to the reference category. Finally, playing at home also displayed positive associations with all dependent variables, while playing opponents with greater win percentages over the prior 10 games was negatively associated with all outcomes. There was no observed relationship between RRI and PF or interaction between competitive season and RRI. Based on these data, RRI positively influences team performance and game outcomes in terms of DIFF, PA, and W/L in recent NBA competition.